SONJA LUEHRMANN, Religion in Secular Archives: Soviet Atheism and Historical Knowledge - Wieland, Alexandra (Archivaria, 2017)
Religion in Secular Archives: Soviet Atheism and Historical Knowledge. SONJA LUEHRMANN. New York: Oxford University Press, 2015. xii, 240 pp. ISBN 978-0-19-994362-3